2019
DOI: 10.1021/acs.langmuir.9b00702
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Activated PEG Surface Segregation Controls the Protein Repellency of Polymers

Abstract: Poly(ethylene glycol) (PEG) is widely used to modulate the hydration states of biomaterials and is often applied to produce non-fouling surfaces. Here, we present X-ray scattering data which show that it is the surface segregation of PEG, not just its presence in the bulk, that makes this happen by influencing the hydrophilicity of PEG-containing substrates. We demonstrate a temperaturedependent trigger that transforms a PEG-containing substrate from a protein-adsorbing to a protein-repelling state. On films o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 52 publications
3
24
0
Order By: Relevance
“…It has been reported that PEG polymers are hydrophilic and can reduce the adsorption of nucleic acids, proteins, and other substances on the nanoparticle surface [ 26 , 27 , 28 ]. The effect of DSPE-PEG2000-N3 on liposome dispersion was investigated by adding different proportions of DSPE-PEG2000-N3 as a liposome component.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that PEG polymers are hydrophilic and can reduce the adsorption of nucleic acids, proteins, and other substances on the nanoparticle surface [ 26 , 27 , 28 ]. The effect of DSPE-PEG2000-N3 on liposome dispersion was investigated by adding different proportions of DSPE-PEG2000-N3 as a liposome component.…”
Section: Resultsmentioning
confidence: 99%
“…This disassembly is consistent with the flat surface layer seen in AFM (Figure ). It is possible that entanglements of the PEG segments on the corona of the nanosphere and the brushes of the PEG chain on the surface of these substrates produce a Velcro effect causing the nanosphere to unravel . This is the opposite of the repulsion of hydrophilic proteins from the near PEG-rich surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible that entanglements of the PEG segments on the corona of the nanosphere and the brushes of the PEG chain on the surface of these substrates produce a Velcro effect causing the nanosphere to unravel. 41 This is the opposite of the repulsion of hydrophilic proteins from the near PEG-rich surfaces. Additionally, interactions between aromatic groups in the nanosphere core and the substrate polymer may result in deformation or disassembly of our nanospheres.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The most prominent molecule that is used to create a hydrophilic surface is poly­(ethylene glycol) (PEG). By PEG coating, the surface becomes rendered polyhydrophilic resulting in reduced protein adsorption. ,, Additionally, the brush structure of the PEG molecules induces steric repulsion of proteins. Chen et al confirmed that the modification of titanium with PEG improves the platelet’s acceptance and inhibits the activation of platelets . Although the PEGylation of surfaces is used routinely for many biomedical applications, some studies have shown that it cannot be generally referred to be a hemocompatible material.…”
Section: Recent Efforts To Reduce Platelet-surface Activationmentioning
confidence: 99%
“…By PEG coating, the surface becomes rendered polyhydrophilic resulting in reduced protein adsorption. 52,55,56 Additionally, the brush structure of the PEG molecules induces steric repulsion of proteins. 57−59 Chen et al confirmed that the modification of titanium with PEG improves the platelet's acceptance and inhibits the activation of platelets.…”
Section: Effect Of Platelet Activation In Medicalmentioning
confidence: 99%